Nematode reproduction and damage to Musa sword suckers and sword sucker derived plants - Speijer, P.R.; Boonen, E.; Vuylsteke, D.R.; Swennen, Rony L.; Waele, D. de (1999)
The susceptibility and sensitivity to Radopholus similis and Helicotylenchus multicintus of 2-month-old plants derived from sword suckers (early screening) and of sword suckers of established 18-month-old mats belonging to 12 Musa genotype was investigated and compared. Differences in nematode population densities and root damage (number of functional roots, percentage of dead roots and necrosis) were observed between the two evaluation trials which suggests a difference host plant response to nematode attack of young root systems compared to older root systems.